Lecturers and librarians in collaboration The common pursuit of scholarly thinking in the Special Education Programme - Bruce, Barbro; Rasmussen, Helen; Zaar, Jessica; Andersson, Lotta (Nordic Journal of Information Literacy in Higher Education, 2013)
<!--[if gte mso 9]> <![endif]--> <!--[if gte mso 9]> <![endif]--> <!--[if gte mso 9]> Normal 0 21 false false false SV X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> <!--[if gte mso 9]> <![endif]--> During 2012 the Special Education Teacher Training Programme at Malmö University ran the education development project "From experience-based practice to scholarly thinking". The background of the project was the fact that the students' practical teaching experience had not been sufficiently utilized and scientifically processed, while at the same time the courses in Philosophy of Science and Research Methodology were perceived to be distancing and difficult to absorb. The aim of the project was to allow theory and practice to mutually enrich one another in a clear manner in the progression towards scholarly thinking. All lecturers of all the courses within the Special Education Programme, met together with two librarians to discuss perceptions of what scholarship is and why a research based approach is important in Special education and in the profession Special education teacher. Together we brainstormed ideas and suggestions of learning activities which together could form a progression to develop a research based approach among students. One idea that has already been launched is Spanarverkstad (a version of Journal Clubs) where articles chosen by students ranged from practical education journals to scholarly journals, are discussed. Another form has been Idea Seminars where representatives from the special education field offer to come up with thesis ideas. Another activity is when lecturers from the Philosophy of Science and Research Methodology courses talks about the research methods that they have personal experience of and perspectives on scholarly thinking. They meet the students in a panel debate where the students have the chance to put forward questions. One developing idea is to encourage students to record their experiences and thoughts in writing. Namely a genre-based pedagogy which could be called something along the lines of "From blog to academic article and vice versa". The aim with the round table discussion is to have the opportunity to exchange experiences, thoughts and ideas of how the collaboration between lecturers and librarians can become a strategic partnership in the pursuit of developing students' scholarly thinking. The round table discussion begins with a presentation of the project "From experience-based practice to scholarly thinking". Afterwards we would like to give the participants the chance to pose questions and discuss how librarians and lecturers can jointly contribute to achieve this goal. How can librarians and lecturers work together to prepare students for a profession where a research-based approach is an important factor in school development? Another point we want to bring into the discussion is what librarians can contribute to a teaching team when it is focusing on planning tutorials for students in higher education? What do lecturers see the librarians' roles as within the team? These are a few examples of questions which could be asked or could be worth developing. <!--[if gte mso 9]> Normal 0 21 false false false SV X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false SV X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->